2022
DOI: 10.1101/2022.03.07.482891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skeletal Muscle TFEB Signaling Promotes Central Nervous System Function and Reduces Neuroinflammation during Aging and Neurodegenerative Disease

Abstract: Skeletal muscle has recently arisen as a novel regulators of Central Nervous System (CNS) function and aging, secreting bioactive molecules known as myokines with proteostasis and metabolism-modifying functions in targeted tissues, including the CNS. Here we report the generation of a novel transgenic mouse with enhanced muscle proteostasis via moderate overexpression of TFEB. We have discovered that the resulting enhanced skeletal muscle proteostasis function can significantly ameliorate proteotoxicity, reduc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 136 publications
(414 reference statements)
8
21
2
Order By: Relevance
“…Indeed, we observed robust reductions in neuroinflammation and rescue of declining neurotrophic signaling in the hippocampus of both aged (24-months-old) and MAPT P301S transgenic mice (8-months-old) with muscle-TFEB overexpression. Furthermore, we also identified sex-dimorphic transcriptional remodeling in the CNS of muscle-TFEB overexpressing mice, with female mice displaying significant upregulation in pathways associated with synaptic physiology, neurotransmitter signaling and voltage-and ion-gated channels, and male mice displaying up-regulation of mitochondrial and ribosomal signaling [5]. We also confirmed that these neuroprotective effects were associated with increased expression and secretion of known CNS-targeting myokine cathepsin B [5].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Indeed, we observed robust reductions in neuroinflammation and rescue of declining neurotrophic signaling in the hippocampus of both aged (24-months-old) and MAPT P301S transgenic mice (8-months-old) with muscle-TFEB overexpression. Furthermore, we also identified sex-dimorphic transcriptional remodeling in the CNS of muscle-TFEB overexpressing mice, with female mice displaying significant upregulation in pathways associated with synaptic physiology, neurotransmitter signaling and voltage-and ion-gated channels, and male mice displaying up-regulation of mitochondrial and ribosomal signaling [5]. We also confirmed that these neuroprotective effects were associated with increased expression and secretion of known CNS-targeting myokine cathepsin B [5].…”
Section: Introductionsupporting
confidence: 60%
“…The muscle-to-brain axis has recently arisen as a powerful regulator of CNS health and function [5][6][7][8][9]. This novel signaling axis is mediated by circulating factors collectively known as 'myokines', which are secreted from skeletal muscle in response to multiple physiological and pathological conditions with high metabolic demand [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huntingtin is expressed in many tissues throughout the body and mutant huntingtin aggregates have been found in multiple tissues ( Van Der Burg et al, 2009 ). Most preclinical work in HD has studied the role of neuronal huntingtin in the brain and peripheral huntingtin in periphery, though new studies in brain-periphery crosstalk have demonstrated that the periphery can affect the brain, especially skeletal muscles ( Ehlen et al, 2017 ; Matthews et al, 2022 ). Our results complement these studies and add to the evidence supporting the importance of brain-periphery crosstalk, as neuronal mutant huntingtin is sufficient to reduce locomotor performance without expression of mutant huntingtin in the muscles themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to this, a comprehensive account of supplementation usage (e.g., Vitamin D3, multivitamin, melatonin, etc.,) and comorbid conditions is equally important since these factors can have confounding effects on biomarkers derived from EVs, especially if there is published literature indicating a certain drug/supplement or condition that could alter the EVs' signature. Lastly, many studies report that exercise results in the release of both general exerkines and exercise-induced myokines (i.e., exerkines coming from skeletal muscle) both in the circulation and in EVs [206][207][208][209]. As such, it would be important to document the physical activity nature of included participants.…”
Section: Documentation Of Pharmacological Treatments Supplementations...mentioning
confidence: 99%